An evaluation of the nutritional status of preschool chldren living in a rural health district : implications for a community based nutrition programme in the Northern Province - Saitowitz, Romy (Department of Paediatrics and Child Health, 2018)
The study aimed to evaluate the nutritional status of pre-school children (0-6 years), and the activities of a local CBNP serving these children, in the Ngwaritsi health district of the Northern Province. The following objectives were identified: o To determine the anthropometric status of children 0-6 years o To determine the dietary intake of children 0-6 years o To evaluate the nutrition services offered to these children by a local CBNP o To make recommendations, based on these findings, for improving existing strategies to address malnutrition in the area.